Phosphogypsum Carbide Recovery - Saydullayev A.A.,; Hamrokulov J.B.,; Saydullayev S.A., (American Journal of Biology and Natural Sciences, 2025)
As the world population increases, the demand for food products is increasing. Land use is important to meet these needs. The fertility of currently used soils is decreasing year by year. This work presents the results of studying the process of obtaining phosphogypsum urea based on phosphogypsum and urea liquefaction. The strength of fertilizer granules obtained by adding phosphogypsum to urea liquefaction in the studied proportions increased from 2.61 to 4.25 MPa, and the pH of the granules decreased from 8.02 to 7.92. The tests showed that the N content in the composition was from 43.97 to 45.94%, the CaO content from 0.09 to 0.87%, and the S content from 0.16 to 1.54%. The resulting fertilizer samples have a significant impact on improving the agrochemical and agrophysical properties of soils and increasing plant productivity.